2005
DOI: 10.1007/s10198-005-0277-2
|View full text |Cite
|
Sign up to set email alerts
|

Costs of hospitalization for severe acute asthma of patients not treated according to guidelines and recommendations

Abstract: This prospective study of 169 adult patients hospitalized for severe acute asthma in four pneumology wards compared the incidence and costs of patients who were managed (group A) or not managed (group P) before hospitalization, according to the guidelines and international recommendations (11 criteria judged by experts). Ambulatory costs were calculated by questioning patients. Valuation of hospital costs was based DRGs weighted by length of stay. The incidence in group P patients was estimated at 70%; A patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 34 publications
(39 reference statements)
4
28
0
Order By: Relevance
“…Stanford and associates reported resources such as nursing care, respiratory therapy, and ED-specific supplies along with equipment use and physician fees to account for the majority of hospital costs of asthma; 44%, 11% and 53% of the costs, respectively [ 36 ]. The results of the cost estimation for asthma hospitalization in Quebec for the year 1994/95 indicated that of the total cost of $23.3 million, the greatest proportion was accounted for by pediatric patients ($11 million) [ 57 ]. Similar findings in a retrospective cohort study also suggested that although teaching hospitals in their study were not found to have higher charges, children's hospitals appeared to be more expensive due to the inherent responsibilities of a teaching hospital, but also due to the fact that they act as regional referral centers with specialized services for children [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stanford and associates reported resources such as nursing care, respiratory therapy, and ED-specific supplies along with equipment use and physician fees to account for the majority of hospital costs of asthma; 44%, 11% and 53% of the costs, respectively [ 36 ]. The results of the cost estimation for asthma hospitalization in Quebec for the year 1994/95 indicated that of the total cost of $23.3 million, the greatest proportion was accounted for by pediatric patients ($11 million) [ 57 ]. Similar findings in a retrospective cohort study also suggested that although teaching hospitals in their study were not found to have higher charges, children's hospitals appeared to be more expensive due to the inherent responsibilities of a teaching hospital, but also due to the fact that they act as regional referral centers with specialized services for children [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The significant contribution of direct healthcare costs due to hospitalization in studies is not surprising given the inherent high costs associated with acute care versus ambulatory care [ 14 , 15 , 20 , 28 , 30 , 36 , 38 , 42 , 48 - 50 , 53 - 57 , 65 , 72 ]. Variations in the cost of hospitalization are likely related to the differences in the socioeconomic environment, that is, the difference in the gross national income per capita, or more specifically differences in salary costs in different countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(26) defined three populations of asthmatic patients: near‐fatal acute asthma, emergency admission for acute asthma, and out‐patients; 37% of the 197 patients admitted to emergency department for acute asthma were considered to be suffering from mild asthma (Table 5). Finally, in a French study (27) of 169 emergency admissions for asthma, asthma was classified as intermittent in nearly 30% of cases and as mild persistent in 20%.…”
Section: Asthma Control and Severe Exacerbations In Mild Asthmamentioning
confidence: 99%
“…Asthma continues to be a national and international health priority. 1,2 A pediatric study in 2011 showed that although the rate of admission for asthma decreased by one-half during a 15-year period, the rate of critical asthma care tripled and hospital costs increased from $6.6 million to $9.5 million for a single state. 3 Two reviews of the Pediatric Health Information System found marked regional variations in the choice of critical asthma medical interventions when children did not improve with standard therapy (inhalation of b-agonists and steroids).…”
mentioning
confidence: 99%